Usulan Interval Preventive Maintenance dan Estimasi Biaya Pemeliharaan Menggunakan Metode Reliability Centered Maintenance dan FMECA - Wirda Hamro Afiva; Fransiskus Tatas Dwi Atmaji; Judi Alhilman (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
ABC is a company engaged in the production of automotive spare parts and accessories, especially motorcycles. The problems faced by the company, there is frequent damage to the CNC Milling A. The company applies preventive maintenance and corrective maintenance activities, but these maintenance activities have not yet run optimally. Therefore, a maintenance system is developed to improve machine reliability. The method used is Reliability Centered Maintenance (RCM), with the aim of determining the optimal maintenance interval and estimation of efficient maintenance costs. RCM is done by analyzing the Failure Modes Effect and Critical Analysis (FMECA). The results of the FMECA analysis are in the form of a Risk Priority Number (RPN) that shows the components of rail bearings, spindle bearings, and hoses as critical components of the system. Through the RCM method, the maintenance policy is generated in the form of 2 scheduled on-condition tasks, 2 scheduled restorations, and 3 scheduled discard tasks with maintenance time intervals in accordance with the task category and can save maintenance costs of IDR 175.602.300.